Comprehensive genetic diversity and genome-wide association studies revealed the genetic basis of avocado fruit quality traits - Li, Jin; Eltaher, Shamseldeen; Freeman, Barbie; Singh, Sukhwinder; Ali, Gul Shad (Frontiers in Plant Science, 2024)
Avocado (Persea americana) is a highly nutritious fruit gaining popularity worldwide. However, its cultivation is currently reliant on a limited number of cultivars with limited genetic diversity. This situation calls for the development of new avocado cultivars with improved horticultural, fruit quality, and nutritional traits, as well as resistance to diseases and pests, and adaptability to changing climatic conditions. The potential of marker-assisted selection in accelerating the development of new avocado varieties offers a ray of hope for the future of avocado cultivation, promising a brighter and more diverse avocado market. This report investigated the genetic diversity and population structure of a diversity panel of 110 avocado accessions. We also conducted genome-wide association studies (GWAS) targeting nine fruit-quality traits using 4,706 high-quality single nucleotide polymorphisms (SNPs) with two different models: GLM (PCA) and MLM (PCA + K). Our analysis revealed three distinct populations, each corresponding to one of the three avocado ecotypes. Phylogenetic analysis showed a close relationship between the Guatemalan and West Indian races, compared to the Mexican race among the selected accessions, supported by population pairwise FST analysis. GWAS identified 12 markers within 11 genomic regions strongly associated with fruit quality traits, including fruit color, shape, taste, and skin texture. Variation explained by these markers ranged from 14.84% to 43.96%, with an average of 24.63%. Annotation analyses of these genomic regions unveiled candidate genes responsible for controlling these traits. These findings improved our understanding of genetic diversity and population structure in avocado germplasm and provided valuable insights into the underlying genetic basis of fruit quality traits. These could significantly impact breeding and parent selection efforts to improve avocado cultivars.